Front Cover: Alanine and Lysine Scans of the LL‐37‐Derived Peptide Fragment KR‐12 Reveal Key Residues for Antimicrobial Activity (ChemBioChem 9/2018). (19th April 2018) - Gunasekera, Sunithi; Muhammad, Taj; Strömstedt, Adam A.; Rosengren, K. Johan; Göransson, Ulf
Abstract : The front cover picture focuses in on a peptide derived from KR‐12 that shows improved antimicrobial activities. The parent peptide is a short fragment of the human cathelidicin LL37. It displays broad‐spectrum activity against pathogenic G+ and G− bacteria, and against fungi. By subjecting KR‐12 to systematic alanine and lysine scans, key residues are revealed that control both activity and selectivity. To further explore activity, double mutants were created: one of these—Q5K, D9A—is in the center of the figure, with a single mutant, and the parent peptides to the right. More information can be found in the full paper by U. Göransson et al. onpage 931 in Issue 9, 2018 (DOI:10.1002/cbic.201700599 ).